Perspektiven des Bergbauerbes im Museum - Farrenkopf, Michael; Siemer, Stefan (2020)
The essays published in this volume, taken from a 2017 conference at the German Mining Museum in Bochum, examine mining heritage with regard to museumization, digitalization, restoration, and object research. At the same time, the volume reflects the diversity of mining’s historical legacy, which extends from associations to large museums of technology.